Heat balancing of direct reforming fuel cells in MGT-SOFC hybrid systems. (March 2019) - Berg, H.P.; Kleissl, M.; Himmelberg, A.; Lehmann, M.; Prechavut, N.; Vorpahl, M.
Abstract: Solid oxide fuel cells convert chemical energy in electrical energy and are highly suitable for the conversion of hydrocarbon based fuels and products from PowerToGas conversions. Embedded in a micro gas turbine-cycle instead of the combustion chamber the heat energy of the injected fuel, released in the SOFC-Stack, can additionally converted into work and by a turbine-generator into electricity. In a compact system, SOFC stacks are designed to realize a direct steam-reforming process inside. In such direct-reforming fuel cell systems the SOFC operating temperature due to the heat demand for reforming, can be reduced to a value in the range of the outlet temperature of the downstream flow (650°C). If the cycle uses a recuperating system, the operating conditions of the SOFC can be realized without additional high-temperature heat exchanger systems. The system with an uncooled turbine, described in [1], just can reach the operating temperature with an additional high-temperature heat exchange. The system described in this publication does not require an additional high-temperature heat exchanger, because the X-value, as the ratio between the exchanged heat quantity and the required amount of heat to complete the MGT-cycle [2] due to the referring process, is nearly zero and can be realized via the inner container wall (of the MLC). The cycle is completed (between the SOFC and the turbine entry) by the heat input of an afterburner. Here the unreacted fuel of the SOFC fuel-stream is used to provide the necessary heat energy for the downstream turbo-generator-system.